Creation of a Comfortable Living Environment in the North of Krasnoyarsk Krai - Kiselev, Timofey; Kiseleva, Olesya; Uspenskaya, Olga (project baikal, 2020)
The article considers the field observations and design in the polar latitudes of Krasnoyarsk Krai. It analyses the contemporary problems of living conditions in the Extreme North, the influence of the comfortable environment on the settlement stability and the prevention of migration out of northern territories, as well as attracting and retaining of young specialists and young people in general in the North. The authors provide the examples of design solutions for creation of contemporary living conditions, the results of the sociological analysis and participatory design that involved inhabitants of the northern territories (Khatanga, Kresty, Zhdanikha).